Mass-producible method for preparation of a carbon-coated graphite@plasma nano-silicon@carbon composite with enhanced performance as lithium ion battery anode. (20th September 2017) - Chen, Hedong; Wang, Zhoulu; Hou, Xianhua; Fu, Lijun; Wang, Shaofeng; Hu, Xiaoqiao; Qin, Haiqing; Wu, Yuping; Ru, Qiang; Liu, Xiang; Hu, Shejun
Abstract: Carbon-coated core-shell structure artificial graphite@plasma nano-silicon@carbon (AG@PNSi@C) composite, applying as lithium ion battery anode material, has been prepared via spray drying method. The plasma nano-silicon (<100 nm), which contained amorphous silicon, was synthesized by radio frequency induction plasma system with the high temperatures processing capability and high quench rates. The artificial graphite in the composite acts as the core which supports the particle and provides electroconductivity, while PNSi attached on the surface of the core, enhances the specific capacity of the composite. The as prepared composite shows superior performance as anode in lithium-ion batteries, regarding to the initial Coulombic efficiency and cycle life. The initial Coulombic efficiency of AG@PNSi@C electrode is 81.0% with a discharge capacity of 553 mAh g −1 and a recharge capacity of 448 mAh g −1 . During cycling, AG@PNSi@C exhibits excellent performance with a very low capacity fading that the discharge capacity maintains 498.2 mAh g −1 and 449.4 mAh g −1 after 250 cycles and 500 cycles. AG@PNSi@C also shows enhanced resistance against high current density. Besides the remarkable electrochemical performances, the facile and mass-producible synthesis process makes the AG@PNSi@C composite very promising for its application in lithium-ion batteries.